MENYONGSONG PEMBERLAKUAN KEWAJIBAN SERTIFIKASI HALAL DI INDONESIA - Achmad Jaka Santos Adiwijaya (JURNAL ILMIAH LIVING LAW, 2019)
In line with the objectives of Indonesia's national developmeent as setforth in the fourth paragraph of the Preamble of the Constitution 1945 which is one of them to achieve the creation of a just and prosperous society based on economic democracy, there has been established an economic system that is developed based on the values of justice, togetherness, equality and benefit in accordance with sharia principles. In this case, among others, the state is obliged to provide protection and guarantees about the halal products used and consumed by the public. Therefore, in 2014, Law Number 33 Year 2014 concerning Halal Product Certification was stipulated. However, this Law has not been fully operated yet although it is enforced for almost 5 years. Two main issues that will be discussed in this short paper are about Indonesia Legal system readiness to integrate sharia (economic) laws within Indonesia Legal System and discussing about how is the Good Legislation Governance practices in the Law making process pertaining Halal Product Certification.